Family presence during resuscitation: Validation of the risk–benefit and self-confidence scales for student nurses. (June 2016) - Bray, Isabelle; Kenny, Gerard; Pontin, David; Williams, Rachel; Albarran, John
Background . There is increasing debate about the advantages and disadvantages of family-witnessed resuscitation. Research about the views of healthcare providers depends upon reliable tools to measure their perceptions. Two tools have been developed for use with nurses (26-item cost-benefit tool, 17-item self-confidence tool).Objectives . Firstly, to validate these tools for use with student nurses in the UK. Secondly, to report on the perceived risks and benefits reported by student nurses, and their self-confidence in dealing with this situation.Methods . A sample of 79 student nurses were invited to complete the tools. Item-total correlations and Cronbach's α were used to determine internal consistency. Factor analysis was computed to assess construct validity. The correlation between the two scales was explored.Results . 69 students completed a questionnaire. Very few had experience of family-witnessed resuscitation. Mean total scores were 3.16 (standard deviation 0.37; range 2.04–4.12) on the risk-benefit scale and 3.14 (standard deviation 0.66; range 1.94–4.82) on the self-confidence scale. Four of the original items were removed from the risk-benefit scale (Cronbach's α 0.86; 95% confidence interval ≥0.82). None were removed from the self-confidence scale (Cronbach's α 0.93; 95% confidence interval ≥0.91). There was a significant correlation between the two scales ( r  = 0.37, p  = 0.002).Conclusions . There is growing evidence that these tools are valid and reliable for measuring student nurses' perceptions about family-witnessed resuscitation.